Business Development Strategies at PT. Jamkrida Bali Mandara to Stay Afloat Relevant in The Digital Transformation Era - Putu Akila Chandra Satya Dewi; Ni Putu Nina Eka Lestari (Eduvest - Journal of Universal Studies, 2024)
This research aims to analyze the implementation of strategic management in the context of digital transformation at PT Jamkrida Bali Mandara, hereinafter referred to as JBM, and its impact on the business model used. With the rapid development of technology, financial institutions such as Jamkrida are faced with the challenge to adapt and innovate in providing services. The method used includes qualitative analysis through interviews and surveys to employees and customers. The results show that the integration of digital transformation not only improves operational efficiency, but also strengthens relationships with customers through more responsive and personalized services. In addition, the use of Business Model Canvas as an analytical tool helps in formulating a more comprehensive strategy, which includes aspects of value proposition, customer segments, and distribution channels. This research provides recommendations for Jamkrida to continue developing technology-based strategies to create a more inclusive and sustainable financial ecosystem.